2003
DOI: 10.1161/01.str.0000044170.46643.5e
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Stroke Referrals From Primary Care, Emergency Room Physicians, and Ambulance Staff Using the Face Arm Speech Test

Abstract: Background and Purpose-Timely referral of appropriate patients to acute stroke units is necessary for effective provision of skilled care. We compared the characteristics of referrals with suspected stroke to an academic acute stroke unit via 3 primary referral routes: ambulance paramedics using a rapid ambulance protocol and stroke recognition instrument, the Face Arm Speech Test; primary care doctors (PCDs); and emergency room (ER) referrals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
319
6
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 435 publications
(361 citation statements)
references
References 23 publications
(16 reference statements)
14
319
6
17
Order By: Relevance
“…Frequent misdiagnosis of stroke has been described among non-neurologist medical providers 23 . The presence of a neurologist in the emergency room has been proposed as a solution to improve this situation 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Frequent misdiagnosis of stroke has been described among non-neurologist medical providers 23 . The presence of a neurologist in the emergency room has been proposed as a solution to improve this situation 24 .…”
Section: Discussionmentioning
confidence: 99%
“…(f) Stroke: Early recognition of stroke using stroke assessment systems can decrease the time interval between onset and arrival at hospital for defi nitive treatment, leading to improved functional outcomes. (38)(39)(40)(41)(42)(43) First aid providers should be trained in the use of stroke assessment systems to recognise the signs and symptoms of stroke. We recommend the use of the FAST (Face, Arm, Speech, Time) stroke assessment system, which is the simplest tool for bystanders, with high sensitivity for the identifi cation of stroke.…”
Section: Medicalmentioning
confidence: 99%
“…Consequentially, EMTs and paramedics have been able to perform better in stroke recognition than the EMD (up to 90% of cases) but the results have varied widely depending on the EMS system in question. After the development of dedicated prehospital stroke scales such as the CPSS , FAST (Harbison et al 2003) and the Los Angeles Prehospital Stroke Screen (LAPSS) (Kidwell et al 2000) In general, FAST and CPSS have been reported to have higher sensitivity than LAPSS while LAPSS clinical items whereas the LAPSS is longer and consists of an interview and clinical section. However, the overall performance of the three major stroke scales has been similar in comparative studies (Tables 6 & 7).…”
Section: Prehospital Recognition Of Acute Strokementioning
confidence: 99%